Chlorophyll degradation effected by lichen substances - Bouaid, K; Vicente, C (ANNALES BOTANICI FENNICI, 1998)
Epiphytic lichens can exert some negative actions on trees, since they penetrate to different degrees into several tissues of the phytophore. Evernia prunastri (L.) Ach. hyphae progress into xylem vessels of Fagus sylvatica, Quercus pyrenaica and Betula alba. This is on the basis of a mechanism through which Lichens inject metabolic inhibitors in the xylem vessels, and, after their translocation in the xylem sap, they reach different organs of the phytophore and produce defoliation. In this report, we have noted that usnic acid is more impermeant than atranorin through the chloroplast membrane of Quercus rotundifolia leaves. On the other hand, we have also noted the degradation of chlorophyll in response to Lichen substances.
Keywords: chlorophyll degradation; Evernia prunastri; lichen phenols; Quercus rotundifolia